Vitamin D Levels and Nutritional Risk Index: Mobility and Mortality After Hip Fracture Surgery (P01-013-19). (13th June 2019) - Hao, Lihong; Schlussel, Yvette; Carson, Jeffrey; Shapses, Sue
Abstract: Objectives: Hip fractures are associated with a high rate of morbidity and mortality, and successful ambulation after surgery is an important outcome in this patient population. This study aims to determine whether 25-hydroxyvitamin D (25(OH)D) or the Geriatric Nutritional Risk Index (GNRI) is associated with short term mortality or ability to walk after hip fracture surgery. Methods: Patients undergoing hip fracture repair were included in this study. Mortality and walking ability were assessed at 30 and 60 days after hip fracture surgery. Pre-operative serum albumin and 25(OH)D were measured. Patients were characterized with 25(OH)D <12 ng/mL, 12 to <20, 20 to <30 or ≥30. GNRI was calculated from albumin and body weight and patients were categorized into major/moderate nutritional risk (<92), low risk (92 to <98) or in good nutritional status (≥98). Results: Of the 290 patients (82 ± 7 years, BMI 25 ± 5 kg/m2), 73% were females. Compared to patients with vitamin D deficiency (<12 ng/mL), those with vitamin D levels in higher categories had increased ability to walk at 30 days ( P  = 0.031): 12 to <20 ng/ml (adjusted odds ratio = 2.61; 95% confidence interval = 1.13–5.99); 20 to <30 ng/ml (3.48; 1.53–7.95); ≥30 ng/ml (2.84; 1.12–7.20). In addition, patients also had increased mobility at 60 days in these same higher vitamin D categories 12 to <20 (2.67; 1.14–6.25); 20 to <30 (3.42; 1.46–8.00); ≥30 ng/ml (3.67; 1.37–9.82) compared to the reference group (<12 ng/mL; P  = 0.028). There was no association of vitamin D with mortality at either time point. GNRI was not associated with mortality or walking ability. Conclusions: In patients with hip fracture, vitamin D deficiency (<12 ng/mL) was associated with reduced ambulation after surgery, whereas GNRI was not associated with any outcomes. Mechanisms that attenuate mobility due to vitamin D deficiency should be examined in future studies. Funding Sources: ONE Nutrition Grant to SAS and JLC.